Taking Power : Women's Empowerment and Household Well-Being in Sub-Saharan Africa - Annan, Jeannie; Donald, Aletheia; Goldstein, Markus; Gonzalez Martinez, Paula; Koolwal, Gayatri (World Bank, Washington, DC, 2019)
This paper examines women's power relative to that of their husbands in 23 Sub-Saharan African countries to determine how it affects women's health, reproductive outcomes, children's health, and children's education. The analysis uses a novel measure of women's empowerment that is closely linked to classical theories of power, built from spouses' often-conflicting reports of intrahousehold decision making. It finds that women's power substantially matters for health and various family and reproductive outcomes. Women taking power is also better for children's outcomes, in particular for girls' health, but it is worse for emotional violence. The results show the conceptual and analytical value of intrahousehold contention over decision making and expand the breadth of evidence on the importance of women's power for economic development.